Penerapan Model Pembelajaran Discovery Learning Untuk Meningkatkan Hasil Belajar Siswa Pada MataPelajaran IPA Kelas V SDN 124 Batuasang Kecamatan Herlang Kabupaten Bulukumba - Arnita M Basri; Rohana Rohana; Hamzah Pagarra (Prodi PGSD FIP UNM, 2018)
This research is a classroom action research that aims to increase learning outcomes IPA by applying discovery learning model. The approach used in this study is qualitative with the type of research is Class Action Research (PTK) is recycled/ cycles that include planning, execution, observation, and reflection. The data analysis used is qualitative . The results showed that there are increases in learning both on the activities of teachers and students as well as student learning outcomes. From this research can be concluded that teacher teaching activities and student learning activities are increase, student learning outcomes in cycle I not yet in the category enough, in cycle II student learning outcomes have increased are in good category and the application of discovery learning learning model in science subjects can improve the learning outcomes of fifth grade V SDN 124 Batuasang Kecamatan Herlang Kabupaten Bulukumba.